Development of a Telehealth Examination for Sport-Related Concussion in the Outpatient Setting. (4th January 2022) - McPherson, Jacob I.; Saleem, Ghazala T.; Haider, Mohammad Nadir; Leddy, John J.; Torres, Daniel; Willer, Barry Stewart
Abstract : Objective: To develop a brief, focused telehealth physical examination for use in the outpatient setting by sports medicine physicians, pediatricians, neurologists, and primary care physicians. Background: Telemedicine has become a key resource for addressing healthcare access limitations for individuals living in rural communities. The COVID-19 pandemic has forced physicians and other healthcare providers to adopt telemedicine practices. Published literature guiding the evaluation of patients with concussion via telemedicine is sparse. Design/Methods: The Buffalo Concussion Physical Examination (BCPE) is a practical and pertinent clinical assessment that helps to diagnose concussion and that has prognostic value when repeated over the first weeks after injury. An interdisciplinary team with experience in telemedicine services utilized a modified-Glaser approach to consensus to translate elements of the BCPE into virtual methods enabling clinicians to provide care to patients over the internet. Results: The Telehealth version of the BCPE (Tele-BCPE) includes an orthostatic intolerance screen, examination of the cranial nerves, and tests of the oculomotor, vestibular and cervical systems. History and examination templates as well as detailed instructions for performance are included. The Tele-BCPE is meant to be used at initial and follow-up visits for patients acutely after concussion as well as in those with prolonged symptoms. Conclusions: We developed a telehealth physical examination to help direct treatment to patients at any stage after concussion and reduce barriers to healthcare access posed by the COVID-19 pandemic and for patients living in rural or underserved areas. Prospective evaluation of the validity and reliability of the Tele-BCPE for the diagnosis and management of patients with concussion is warranted.